Inflammatory markers and the risk of idiopathic sudden sensorineural hearing loss: A Mendelian randomization study - Zhou, Tingfeng; Chen, Mengjiao; Yuan, Ziyi; Xia, Zhigang; Zhang, Shurou; Zhang, Ziheng; Chen, Huanqi; Lin, Renyu (Frontiers in Neurology, 2023)
Background Observational studies suggest that inflammatory markers may increase the risk of idiopathic sudden sensorineural hearing loss (ISSHL). However, the causal relationship between the two has not been established. We sought to assess the possible causal effect between several genetically predicted inflammatory markers and ISSHL by Mendelian random (MR) analysis. Methods We extracted single nucleotide polymorphisms (SNPs) associated with C-reactive protein (CRP), Tumor necrosis factor-α (TNF-α), and fibrinogen from abstract data from the European Individual Large genome-wide association studies (GWAS). Genetic data for ISSHL were obtained from the FinnGen study (n = 196,592). Effect estimates were assessed using inverse variance weighting (IVW) as the primary method. Sensitivity analyses were performed using weighted median, MR-Egger, and MR-PRESSO to evaluate heterogeneity and pleiotropy. Results In the random-effects IVW approach, there was a significant causal relationship between genetic susceptibility to CRP levels and ISSHL (OR = 1.23, 95% CI = 1.02–1.49, P = 0.03). In contrast, genetic TNF-α and fibrinogen were not risked factors for ISSHL (OR = 1.14, 95% CI = 0.88–1.49, P = 0.30; OR = 0.74, 95% CI = 0.07–7.96, P = 0.30; OR = 1.05, 95% CI = 0.88–1.25, P = 0.59). All the above results were consistent after validation by different Mendelian randomization methods and sensitivity analyses. Conclusion This Mendelian randomization study provides causal evidence that CRP is a risk factor for ISSHL, while TNF-α and fibrinogen do not increase the risk for ISSHL Introduction.